If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(6z + -1) + -3(z + 3) = 11(z + 1) Reorder the terms: 5(-1 + 6z) + -3(z + 3) = 11(z + 1) (-1 * 5 + 6z * 5) + -3(z + 3) = 11(z + 1) (-5 + 30z) + -3(z + 3) = 11(z + 1) Reorder the terms: -5 + 30z + -3(3 + z) = 11(z + 1) -5 + 30z + (3 * -3 + z * -3) = 11(z + 1) -5 + 30z + (-9 + -3z) = 11(z + 1) Reorder the terms: -5 + -9 + 30z + -3z = 11(z + 1) Combine like terms: -5 + -9 = -14 -14 + 30z + -3z = 11(z + 1) Combine like terms: 30z + -3z = 27z -14 + 27z = 11(z + 1) Reorder the terms: -14 + 27z = 11(1 + z) -14 + 27z = (1 * 11 + z * 11) -14 + 27z = (11 + 11z) Solving -14 + 27z = 11 + 11z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-11z' to each side of the equation. -14 + 27z + -11z = 11 + 11z + -11z Combine like terms: 27z + -11z = 16z -14 + 16z = 11 + 11z + -11z Combine like terms: 11z + -11z = 0 -14 + 16z = 11 + 0 -14 + 16z = 11 Add '14' to each side of the equation. -14 + 14 + 16z = 11 + 14 Combine like terms: -14 + 14 = 0 0 + 16z = 11 + 14 16z = 11 + 14 Combine like terms: 11 + 14 = 25 16z = 25 Divide each side by '16'. z = 1.5625 Simplifying z = 1.5625
| 9x-(4x-5)-(-6x+1)= | | 22=0 | | 11x-77=0 | | 3x^2-25x+42=0 | | 275m^2+396n^2=0 | | 4y+112=180 | | x^2-x-48=16 | | 0.5(x-0.08)=0 | | x/3=3x-1 | | ln(x)+ln(8x)=-3 | | 5y+20=0 | | 5b+7b=60 | | s^2-12s+36= | | (x-2)/3=8 | | (x-2)/3-5=3 | | 4x^3+12x^2+10x+10=0 | | x-2/3-5=3 | | 2x+30+x= | | 24=-8(0.3p+9) | | 4(3x-2)=(6x+6) | | 4X+37+9X=180 | | X=45(16) | | 29x^2-7x=0 | | 0.50x+0.45(90)=0.25(124) | | 5x+8-12=-6x-2x+3 | | -4x-6+x=-2x+6-10 | | 0(n)=2n-1 | | -8(v+4)+2v+6=7v+9 | | (x+7)(x+6)= | | 4x+11=77x-7 | | 3x+15=3x+3 | | 3x^2-6=4x |